(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2008)
Contemporary knowledge degree of mire vegetation of Ukraine is illustrated. It is proved that study of mire vegetation is connected with development of scientific direction of peat land science and with decision of applied tasks for the national economy. Results of investigations and achievements of Ukrainian school of the peat land science in the geobotanical, stratigraphic and phytosozological directions are characterized as well as urgent tasks of the further works.